Vivienda de interés social progresiva y sostenible, como mecanismo de rehabilitación urbana y construcción social en el barrio Villa Resistencia en Ibagué, Tolima. (2024)
Research project that supports the hypothesis of the applicability of progressive social housing with sustainable characteristics, through an architectural prototype that seeks, through a social housing development, to have a percentage and favorable impact on the housing deficit figures in Colombia, The application of urban development proposed through a basic scheme for the city of Ibagué Tolima aims to demonstrate that it is possible to apply more than one sustainable component in social housing, aligning with the sustainability and energy transition policies advanced by the current national government of Colombia.